A luta pelos direitos humanos: o Centro de Defesa dos Direitos Humanos de Osasco (1977-1983) - Camargo, Lucas Alves de (2017)
The context of this master thesis aims to understand the creation process of formation of human rights movement in Osasco’s city. This study also try to elucidate the actuation of The Center for the Defense of Human Rights of Osasco (CDDHO) and the communities whom participated in the fight for human rights in the present area, between the years 1977-1983. In this period, members of Osasco’s city population associated to ecclesial communities and organized movements in the neighborhoods set up a network of human rights activities that made possible the creation of The Center for the Defense and its structuring in several communities of the city. An intense network of collaboration from the base communities would reach the Movements organized in the influence area of the Catholic Church. In this context, the CDDHO built human rights practices for deal with possible transgressions existing, in their project, they developed legal and community actuations. We expect to visualize the construction of the practices through their claims and through their relations with the State institutions